Cryoglobulinemic vasculitis as a rare complication of rheumatoid arthritis : a case report - Gaukhar Bakhtiyarova; Mehtap Tinazli (National Scientific Medical Center, 2017)
Cryoglobulinemic vasculitis (CV); is a disease characterized by cryoglobulin-containing immunodeposits that often involve small vessels of the skin and glomeruli. It is considered to be a rare disorder. There are few cases identified in patients with rheumatoid arthritis (RA) suffering from immunological disorders such as Sjogren's Disease and infectious agents such like as human immunodeficiency virus (HIV) or hepatitis C virus (HCV) infection. We wanted to share a case where we think of cryoglobulinemic vasculitis with rheumatoid arthritis at 50 years old. He applied to us with cyanosis fingertips and severe pain in his hand. Clinical features were assessed by laboratory and nailfold capillaroscopy and CV was diagnosed. Then the patient was treated with intravenous Iloprost for 5 consecutive days, nifedipin and antiagregan. Clinically, the patient presented with a significant reduction of pain and decrease of fingertips ulsers after the second monthly treatment.